L-plastin is involved in NKG2D recruitment into lipid rafts and NKG2D-mediated NK cell migration - Serrano-Pertierra, Esther; Cernuda-Morollón, Eva; Brdička, Tomáš; Hoøejši, Václav; López-Larrea, Carlos (Journal of leukocyte biology, 2014)
Membrane rafts are microdomains of the plasma membrane that have multiple biological functions. The involvement of these structures in the biology of T cells, namely in signal transduction by the TCR, has been widely studied. However, the role of membrane rafts in immunoreceptor signaling in NK cells is less well known. We studied the distribution of the activating NKG2D receptor in lipid rafts by isolating DRMs in a sucrose density gradient or by raft fractionation by β-OG-selective solubility in the NKL cell line. We found that the NKG2D-DAP10 complex and pVav are recruited into rafts upon receptor stimulation. Qualitative proteomic analysis of these fractions showed that the actin cytoskeleton is involved in this process. In particular, we found that the actin-bundling protein L-plastin plays an important role in the clustering of NKG2D into lipid rafts. Moreover, coengagement of the inhibitory receptor NKG2A partially disrupted NKG2D recruitment into rafts. Furthermore, we demonstrated that L-plastin participates in NKG2D-mediated inhibition of NK cell chemotaxis.
Keywords: Microfilament Proteins; RNA interference; Multiprotein Complexes; Signal Transduction; mikrofilamenta; lektinové receptory NK-buněk - podrodina K; malá interferující RNA; Humans; Cells, Cultured; Proteome; lidé; RNA Interference; Detergents; lektinové receptory NK-buněk - podrodina C; proteom; Cell Membrane; Membrane Microdomains; signální transdukce; membránové mikrodomény; buněčná membrána; mikrofilamentové proteiny; RNA, Small Interfering; Chemotaxis, Leukocyte; Killer Cells, Natural; multiproteinové komplexy; NK Cell Lectin-Like Receptor Subfamily C; Actin Cytoskeleton; chemotaxe leukocytů; centrifugace - gradient hustoty; buňky NK; detergenty; kultivované buňky; Receptors, Immunologic; NK Cell Lectin-Like Receptor Subfamily K; Centrifugation, Density Gradient; receptory imunologické